Serial sisters, friends and colleagues. Spanish female choral fiction on broadcast television and VOD platforms (1990-2019) - Ruiz Muñoz, María Jesús; Pérez Rufí, José Patricio (Estudios sobre el Mensaje Periodístico, 2020)
This paper proposes an analysis of those Spanish television series starring women in a choral way from a gender perspective. The main objective of this research is to locate and catalog the female choral series produced in Spain and broadcast between 1990 and 2019 by national public broadcast television, the main comercial broadcast television and VOD platforms. Secondly, we want to analyze the evolution of this kind of television series from their formal features and from the narrative elements that define the female characters represented. In order to achieve these aims, we have combined in the design of this study quantitative and qualitative analysis methodologies. The results reveal an evolution that goes from comedy and a stereotyped representation of women to more diversed television series with a more complex configuration of their female main characters.